The Influence of Interactive Learning Media with a Digital Story Telling Approach on Student Learning Outcomes in Informatics Subject at SMPN 5 Padang Panjang - Hafizah, Anisa; Efrizon, Efrizon; Dewi, Ika Parma; Marta, Rizkayeni (Jurnal Pengabdian Nusantara, 2025)
The rapid advancement of technology in the globalization era has transformed education, emphasizing the integration of innovative tools to enhance learning quality. This study investigates the influence of interactive learning media using a digital storytelling approach on student learning outcomes in Informatics at SMPN 5 Padang Panjang. It combines narratives with multimedia elements like images, audio, video, and animations to make learning more engaging and meaningful. Employing a quantitative quasi-experimental design, this research involved 62 grade VIII students: 31 in the experimental group (using interactive digital storytelling media) and 31 in the control group (conventional methods). Data were collected via pre- and post-tests, analyzed using Shapiro-Wilk for normality (Sig. > 0.05, confirming normal distribution), Levene's test for homogeneity (Sig. = 0.103 > 0.05, indicating equal variances), and independent sample t-test for hypothesis testing. Results revealed a significant difference in post-test scores: the experimental group's mean was 87.94 (SD = 7.711), compared to the control group's 82.29 (SD = 10.706). The t-test yielded t_count = 2.38 > t_table = 1.671 (df = 60, α = 0.05, Sig. = 0.020), rejecting the null hypothesis and confirming a positive, significant effect. Students in the experimental group showed high enthusiasm and active participation, particularly in understanding Computer Systems material.